Russian equity market linkages before and after the 1998 crisis: evidence from time-varying and stochastic cointegration tests - Brian M. Lucey; Svitlana Voronkova (Bank of Finland, Institute for Economies in Transition (BOFIT), 2005)
This paper examines the relationships between the Russian and other Central European (CE) and developed countries' equity markets over the 1995-2004 period.Along with the traditional Johansen and Juselius (1990) multivariate cointegration tests, we apply novel cointegration approaches, including Gregory-Hansen (1996) test, which allows for a structural break in the relationships, as well as the newly developed stochastic cointegration test by Harris, McCabe and Leybourne (2002) and the non-parametric cointegration method of Breitung (2002).The latter tests point to a significant agreement that in the aftermath of the Russian crisis of 1998 there was an increasing degree of comovements of the Russian market with other developed markets, but not with CE developing markets.This result is further confirmed by dynamic conditional correlation modeling, which allows us to investigate graphically the evolution of comovements in the system.The results of detailed cointegration analysis suggest a. that the time-varying nature of equity markets comovements should be explicitly accounted for while modeling long run relationships b. that there is a decline in diversification benefits for foreign investors seeking to invest in Russian equities over the long horizon.
URN:NBN:fi:bof-201408072179
Keywords: G10; G15; 330; Stock Market Integration; CEE Stock markets; Russian Stock Market; Cointegration